British Thoracic Society guideline for bronchiectasis in adults. Issue 1 (28th December 2018) - Hill, Adam T; Sullivan, Anita L; Chalmers, James D; De Soyza, Anthony; Elborn, J Stuart; Floto, R Andres; Grillo, Lizzie; Gruffydd-Jones, Kevin; Harvey, Alex; Haworth, Charles S; Hiscocks, Edwin; Hurst, John R; et al.
Abstract : The full British Thoracic Society Guideline for Bronchiectasis in Adults is published in Thorax . The following is a summary of the recommendations and good practice points. The sections referred to in the summary refer to the full guideline. The appendices are available in the full guideline.